Health-Related Quality of Life and Mental Health in Primary Aldosteronism: A Systematic Review - Velema, Marieke S.; de Nooijer, Aline H.; Burgers, Vivian W. G.; Hermus, Ad. R. M. M.; Timmers, Henri J. L. M.; Lenders, Jacques W. M.; Husson, Olga; Deinum, Jaap (Hormone and Metabolic Research, 2017)
The aim of this review was to determine the impact of primary aldosteronism on health-related quality of life (HRQoL) and mental health. We performed a systematic literature search up to July 2017 in six electronic databases. First, we screened the articles derived from this search based on title and abstract. Second, the selected studies were systematically reviewed and checked for our predefined inclusion criteria. The search yielded 753 articles, of which 15 studies met our inclusion criteria. Untreated patients with primary aldosteronism showed an impaired physical and mental HRQoL as compared to the general population. Multiple domains of HRQoL were affected. This applied to patients with both an aldosterone-producing adenoma and bilateral adrenal hyperplasia. Adrenalectomy improves HRQoL. Conflicting results have been reported on the extent of this improvement, the improvement after initiation of medical treatment, and whether there is a difference in HRQoL after both treatments. Similarly, psychopathological symptoms of anxiety, demoralization, stress, depression and nervousness were more frequently reported in untreated patients with primary aldosteronism than in the general population and patients with hypertension. Also an impaired sleep quality has been reported. Improvement of these symptoms was observed after treatment with both adrenalectomy and mineralocorticoid receptor antagonists. This review shows that HRQoL is impaired and psychopathology is more frequently reported in patients with primary aldosteronism. This seems to be at least partly reversible after treatment but the extent of improvement remains unknown. To assess HRQoL in these patients more precisely a primary aldosteronism-specific HRQoL questionnaire is required.
Keywords: hyperaldosteronism; patient-reported outcome; psychopathology; literature search